SARS-CoV-2 modulates virus receptor expression in placenta and can induce trophoblast fusion, inflammation and endothelial permeability - Agostinis, Chiara; Toffoli, Miriam; Spazzapan, Mariagiulia; Balduit, Andrea; Zito, Gabriella; Mangogna, Alessandro; Zupin, Luisa; Salviato, Tiziana; Maiocchi, Serena; Romano, Federico; Crovella, Sergio; Fontana, Francesco; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 is a devastating virus that induces a range of immunopathological mechanisms including cytokine storm, apoptosis, inflammation, complement and coagulation pathway hyperactivation. However, how the infection impacts pregnant mothers is still being worked out due to evidence of vertical transmission of the SARS-CoV-2, and higher incidence of pre-eclampsia, preterm birth, caesarian section, and fetal mortality. In this study, we assessed the levels of the three main receptors of SARS-CoV-2 (ACE2, TMPRSS2, CD147) in infected and healthy placentae. Moreover, we measured the effects of Spike protein on placental cell lines, evaluating also their susceptibility to infection. We report that SARS-CoV-2 negative placentae showed elevated levels of CD147 and considerably low amount of TMPRSS2, making them non-permissive to infection. SARS-CoV-2 infection upregulated TMPRSS2 expression in syncytiotrophoblast and cytotrophoblast cells, thereby rendering them amenable to infection. The non-permissiveness of placental cells can be due to their less fusogenicity due to infection. We also found that Spike protein was capable of inducing pro-inflammatory cytokine production, syncytiotrophoblast apoptosis and increased vascular permeability. These events can elicit pre-eclampsia-like syndrome that marks a high percentage of pregnancies when mothers are infected with SARS-CoV-2. Our study raises important points relevant to SARS-CoV-2 mediated adverse pregnancy outcomes.